A Study on the Construction and Validation of Pathways to Sustainable Participation in Outdoor Activities Among Chinese Elderly Individuals - Jia Wei; Mohd Johari Mohd Yusof; Shureen Faris Abdul Shukor (European Journal of Investigation in Health, Psychology and Education)
The objective of this study was to propose an analysis pathway that illustrates the psychological mechanism and corresponding environmental motivators affecting the frequency and duration of outdoor activity participation among older adults in China. Firstly, based on the transtheoretical model (TTM) theory and the environmental psychological approach, a literature review was conducted to select the model variables and ensure that they correspond to the requirements of the stage of change construct and the temporal dimension of the TTM theory. Secondly, the variables mentioned above were rearranged according to the perception, action, experience, and emotion stages of the individual psychological mechanism process and the environmental quality improvement outcome to develop the hypothetical model. Subsequently, a confirmatory factor analysis was carried out to test the hypotheses and validate the model based on the survey data collected in Chengdu City, China. Finally, a total of 372 valid questionnaires were received. After analyzing the collected data, the configuration index relationship of the hypothesis model was validated. In conclusion: Through slicing control of environmental factors in diverse human-environmental interaction stages under the guidance of the stage-based behavioral analysis discipline, this study explores an analysis pathway for upgrading outdoor environment facilities to enhance the attraction and attachment characteristics of the environment and, in turn, promote the sustainability of the outdoor activities performed by older people.